Heavy Metal Concentration in Mangrove Soils under Sonneratia caseolaris Trees: The Case of Kampung Kuantan Fireflies Park - Laurna Nyangon; Seca Gandaseca; Samsuri Abdul Wahid Wahid; Mohamad Azani Alias (Jurnal Sylva Lestari, 2023)
The local ecosystem potentiality is pressurized by the getting up heavy metal concentrations, especially in Kampung Kuantan Fireflies Park. This mangrove forest park, which is dominated by Sonneratia caseolaris, is a well-known place to visit for people who like nature in Kuala Selangor Peninsular Malaysia. However, the investigations on heavy metal concentration in mangrove soils under S. caseolaris are still limited.  This study aims to find out the concentration of heavy metal in mangrove soil under S. caseolaris.  The soil samples were taken from under S. caseolaris trees zone. Five plots were built up on mangrove soils through the Selangor River. Five sub-plots, each measuring 2 m ´ 2 m, were made for sample collection in each plot. The heavy metal contents and the geo-accumulation index (I-geo) were evaluated. As the results, the concentration of heavy metals on soils such as zinc (Zn), copper (Cu), lead (Pb), chromium (Cr), and cadmium (Cd) under the S. caseolaris trees of 240.24 mg/kg, 6.89 mg/kg, 25.46 mg/kg, 34.88 mg/kg, and 0.14 mg/kg, respectively.  The I-geo ratio indicated that the soils have low heavy metal deposits, with Cd having the lowest concentration and Zn having the highest. There is a significant difference between Zn and Cr concentrations on the soils in five plots, but there are no significant differences for Cu, Pb, and Cd. In general, the heavy metal contents throughout the sampling area were considered not polluted, since the amount of trace elements in the soil was relatively low compared to the average limit. Keywords: heavy metal, Kampung Kuantan Fireflies Park, Kuala Selangor, mangrove, Sonneratia caseolaris